Identification of direct targets of serine/arginine-rich 45 protein isoforms by TRIBE (Targets of RNA-binding proteins Identified By Editing) in Arabidopsis thaliana - Huynh, Nikki, author; Reddy, A. S. N., advisor; Garrity, Deborah, committee member; Wilusz, Jeffrey, committee member (Colorado State University. Libraries, 2021)
To view the abstract, please see the full text of the document.